Hydrogel capable of absorbing grease as well as preparation method and application of hydrogel
Through wet ultrafine grinding and high shear mixing to form an ultrafine polysaccharide glue solution, combined with microwave vacuum drying and spray fluidized bed granulation technology, honeycomb hydrogel with high efficiency of grease absorption and strong water absorption performance is prepared, and the solution is to solve the problem of The problem of insufficient adsorption capacity of existing hydrogels in oils.
Patent Information
- Application Number
- CN202510024797.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing hydrogels have obvious shortcomings in oil adsorption capacity, making it difficult to effectively control weight.
By mixing the polysaccharide glue with water and superfine grinding, an ultrafine polysaccharide glue solution is formed, and sprayed at high pressure on the surface of cellulose or its derivatives for high shear mixing to form microgroups. Then, microwave vacuum drying is used to form a honeycomb structure, and the water absorption performance and grease absorption capacity of the hydrogel are further enhanced through spray fluidized bed granulation technology.
It significantly enhances the adsorption ability of the hydrogel to water and grease, improves the bulk density and physical crosslinking strength, reduces production energy consumption and improves production efficiency, and achieves efficient oil absorption and satiety.
Smart Images

Figure CN119409994A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer compounds, relates to a composition of polymer compounds, and specifically relates to a grease-absorbing hydrogel and a preparation method and application thereof. Background Art
[0002] The basic principle of weight loss is that the calories consumed are less than the calories burned. Meal replacement foods are popular in the weight loss circle as a low-calorie solution. They are characterized by low calories and come in the form of instant powder, cakes, and solid bars. The common feature of meal replacement foods is that they don’t taste very good. At the same time, if the consumer only eats meal replacement foods, he or she will not only get hungry easily, but also cannot enjoy delicious meals, making it difficult to stick to it. Therefore, a weight control product with a super high water absorption multiple that has no (or very low) calories, can increase the consumer’s satiety, and reduce food intake is an ideal choice for weight loss.
[0003] Chinese patent CN111772180A discloses a high expansion coefficient weight control product, the raw materials of which are konjac glucomannan, pectin, bran and proanthocyanidins. The molecules of these raw materials are combined by hydrogen bonds to form a three-dimensional network structure. After consumption, they absorb water in the stomach and expand rapidly, increasing the consumer's sense of fullness and reducing food intake, thereby achieving the purpose of weight loss or weight control. The weight control product has a low water absorption multiple of only about 10 to 15 times. In order to achieve a sense of fullness, you need to eat more, but the bran itself has a high calorie content (282 kcal / 100 g), and it is not advisable to eat too much. Chinese patent CN115154407A discloses a chitosan linseed gum cross-linked hydrogel, the raw materials of which include chitosan, linseed gum and calcium salt. The carboxyl groups contained in the linseed gum can electrostatically interact with the ammonium ions generated when the chitosan is dissolved in an acidic solution, thereby forming physical cross-linking sites. At the same time, the galacturonic acid contained in the linseed gum is located on the main chain of the molecule and can contact with the calcium ions to form a bridging effect, which helps to form a three-dimensional network of the hydrogel. When the chitosan linseed gum cross-linked hydrogel is used as a gastric filler, it can achieve a certain swelling ratio in acidic gastric juice. After entering the alkaline colon environment, the hydrogel can collapse, has pH sensitivity, and provides a sense of fullness. However, the chitosan linseed gum cross-linked hydrogel has a relatively low swelling in the stomach and provides a limited sense of fullness. Chinese patent CN113854567A discloses an edible hydrogel and a preparation method thereof, wherein a dibasic acid and a polysaccharide or a polysaccharide derivative are dissolved in water, dried at a relatively high temperature, and chemically cross-linked by an esterification reaction to prepare an edible hydrogel. The edible hydrogel prepared by the method is a chemically cross-linked polymer compound, and since the amount of water added is several to dozens of times the amount of solid solute added, the energy consumption required for drying is high, and the production capacity and efficiency are low. Chinese patent CN17179281A discloses a composite gel, wherein the composite gel is prepared by dissolving pectin and cellulose or its derivatives in a large amount of water, and then physically cross-linking the gel by high-temperature drying. Since pectin is a dietary fiber that is poorly soluble in water and has poor solubility, a large amount of pectin needs to be added to water to increase the contact area and entanglement efficiency of pectin and cellulose or its derivatives to a certain extent, and the physical cross-linking is uneven, so the formed gel has poor water absorption performance and uneven storage modulus. The increase in fat content is one of the important reasons for human weight gain. The above hydrogel products have obvious deficiencies in their ability to adsorb fat. In order to effectively control weight, it is urgent to develop a hydrogel product that can efficiently absorb fat, has high safety and strong water absorption capacity. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a hydrogel for absorbing oil and fat, and a preparation method and application thereof, wherein a polysaccharide gum is mixed with water and then ultrafinely ground by wet method, high shear mixing is adopted to make the polysaccharide gum evenly penetrate into the interior of cellulose or its derivatives to form micelles, microwave vacuum drying is adopted to cause the micelles to form a honeycomb structure, and finally ultrapure water is sprayed and dried, thereby enhancing the water absorption performance and oil absorption capacity of the hydrogel, improving the stacking density, and greatly reducing the production energy consumption and improving the production efficiency.
[0005] The purpose of the present invention is achieved by at least one of the following technical solutions.
[0006] The first aspect of the present invention provides a method for preparing a hydrogel for absorbing fat, comprising the following steps: (1) Mixing polysaccharide gum with water to obtain a mixed solution, and wet-milling the mixed solution to form an ultrafine polysaccharide gum aqueous solution; the polysaccharide gum is high-ester pectin or a mixture of high-ester pectin and xanthan gum; the molecular weight of the high-ester pectin is 20,000-200,000, and the degree of esterification of the high-ester pectin is 58%-62%; the molecular weight of the xanthan gum is 1 million-2 million; the particle size of the polysaccharide gum in the ultrafine polysaccharide gum aqueous solution is less than 10 μm; (2) spraying the ultrafine polysaccharide glue solution on the surface of cellulose or its derivatives by high-pressure atomization, and high-shear mixing to make the ultrafine polysaccharide glue solution penetrate into the interior of cellulose or its derivatives and bond to form micelles; the cellulose or its derivatives are sodium carboxymethyl cellulose or a mixture of sodium carboxymethyl cellulose and hydroxyethyl cellulose; the molecular weight of the sodium carboxymethyl cellulose is 20,000-80,000, and the degree of substitution of the sodium carboxymethyl cellulose is 0.7-0.9; the molecular weight of the hydroxyethyl cellulose is 100,000-200,000, and the degree of substitution is 1.3-1.5; the size of the micelles is 0.1-1 mm; (3) drying the micelles by microwave vacuum drying to form honeycombed micelles; (4) Using a spray fluidized bed granulation technology, water is sprayed on the surface of the honeycomb micro-clusters at high pressure and dried to obtain a hydrogel that absorbs oil; the process parameters of the spray fluidized bed granulation technology are an inlet air temperature of 10-30°C, a fan frequency of 20-50Hz, and an atomized water flow rate of 10-20g / min.
[0007] Furthermore, in step (1), the water is ultrapure water, which can avoid the influence of other ions and other substances and is conducive to the formation of a physical cross-linked network of the hydrogel.
[0008] Furthermore, in step (1), the concentration of the polysaccharide glue in the ultrafine polysaccharide glue aqueous solution is 0.01 kg / L~0.1 kg / L.
[0009] Furthermore, in step (1), the mass ratio of the high ester pectin to the xanthan gum is greater than or equal to 3:1.
[0010] Furthermore, in step (1), the mass ratio of the high ester pectin to the xanthan gum is 3:1 or 4:1.
[0011] Furthermore, in step (1), the rotation speed of the wet ultrafine grinding is 1000-1500 rpm, and the time of the wet ultrafine grinding is 30-60 min.
[0012] Furthermore, in step (1), the equipment used for the wet ultrafine grinding is a sand mill.
[0013] Furthermore, in step (2), the mass ratio of sodium carboxymethyl cellulose to hydroxyethyl cellulose is 10-15:4.98-9.98.
[0014] Furthermore, in step (2), the mass ratio of sodium carboxymethyl cellulose to hydroxyethyl cellulose is 15:4.98 or 10:9.98.
[0015] Furthermore, in step (2), the rotation speed of the high shear mixing is 1000-1500 rpm, and the time of the high shear mixing is 5-10 min.
[0016] Furthermore, in step (2), the equipment used for high shear mixing is a high-speed shear mixer.
[0017] Furthermore, in step (2), the mass ratio of the polysaccharide glue in the ultrafine polysaccharide glue aqueous solution to the mass ratio of the cellulose or its derivative is 0.01-0.1:9.9-9.99.
[0018] Furthermore, in step (2), the mass ratio of the polysaccharide glue in the ultrafine polysaccharide glue aqueous solution to the mass ratio of the cellulose or its derivative is 0.02:19.98 or 0.2:19.8.
[0019] Furthermore, in step (3), the vacuum degree of the microwave vacuum drying is -98.0 kPa to -100.0 kPa, the temperature of the microwave vacuum drying is 28 to 44° C., and the time of the microwave vacuum drying is 0.5 to 1 h.
[0020] Furthermore, in step (4), the drying is boiling drying in a fluidized bed, and the drying time is 0.5 to 1 hour.
[0021] Furthermore, in step (4), the water used in the high-pressure atomization spraying is ultrapure water.
[0022] Furthermore, the bulk density of the oil-absorbing hydrogel is 0.5-0.7 g / ml.
[0023] The second aspect of the present invention provides a grease-absorbing hydrogel prepared by any of the preparation methods described above, wherein the grease-absorbing hydrogel has a honeycomb structure.
[0024] Furthermore, the bulk density of the oil-absorbing hydrogel is 0.5-0.7 g / ml.
[0025] The third aspect of the present invention provides a fat-absorbing hydrogel prepared by any one of the preparation methods described in the first aspect of the present invention or the fat-absorbing hydrogel provided by the second aspect of the present invention, and its use in preparing foods, medicines or health products with the effects of controlling diet, inducing satiety and losing weight.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) In the preparation method of the present invention, a polysaccharide gum with a specific lower molecular weight is mixed with water and then wet ultrafine ground. Compared with conventional polysaccharide gums, the solubility is greatly improved, and the particle size of the polysaccharide gum is significantly reduced, which can increase the contact area, collision probability and mixing uniformity between the polysaccharide gum and cellulose or its derivatives, reduce the amount of polysaccharide gum used, reduce production costs, and improve physical cross-linking efficiency; at the same time, the collision probability and contact area between the polysaccharide gum and oil in the hydrogel can be increased, thereby improving the hydrogel's ability to absorb oil.
[0027] (2) In the preparation method of the present invention, an ultrafine polysaccharide glue aqueous solution is sprayed onto the surface of cellulose or its derivatives, and high shear mixing is used to make the polysaccharide glue with very small particle size (<10 μm) evenly penetrate into the interior of cellulose or its derivatives. Since the surface of the polysaccharide glue has a certain amount of moisture, it is beneficial for the polysaccharide glue and the interior of the cellulose or its derivatives to adhere to form micelles. The micelles formed by the polysaccharide glue and the cellulose or its derivatives are subjected to microwave vacuum drying. Compared with hot air drying, the interior of the micelles is evenly heated and expands to form a honeycomb structure under vacuum treatment. The honeycomb structure and the polysaccharide glue with very small particle size cooperate with each other to significantly enhance the adsorption capacity of the hydrogel for water and oil. At the same time, microwave vacuum drying significantly reduces the drying time and reduces the process energy consumption.
[0028] (3) In the preparation method of the present invention, ultrapure water is sprayed on the honeycomb microclusters using a fluidized bed, and drying can shrink the pore size of the honeycomb structure, thereby increasing the packing density and physical cross-linking strength of the hydrogel. Compared with the method without spraying ultrapure water, the hydrogel of the same mass has a smaller volume (higher packing density) and is easier for the user to swallow.
[0029] (4) The hydrogel provided by the present invention uses safe raw materials, does not undergo chemical reactions during the preparation process, and no new substances are generated. Therefore, it has no potential toxicity and can be used in the preparation of weight loss drugs, foods or health products.
[0030] (5) The unit adsorption capacity of the hydrogel provided by the present invention for oil is more than 16 ml / g, which can effectively reduce the body's absorption of oil and fat and achieve a weight loss effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the composite gel 1 prepared in Example 1. DETAILED DESCRIPTION
[0032] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0033] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those of ordinary skill in the art to which the present invention belongs.
[0034] The oil-absorbing hydrogel of the present invention is a composition of polysaccharides and their derivatives.
[0035] In the present invention, a method for preparing a hydrogel for absorbing oil and fat comprises the following steps: (1) Mixing polysaccharide gum with water to obtain a mixed solution, and wet-milling the mixed solution to form an ultrafine polysaccharide gum aqueous solution; the polysaccharide gum is high-ester pectin or a mixture of high-ester pectin and xanthan gum; the molecular weight of the high-ester pectin is 20,000-200,000, and the degree of esterification of the high-ester pectin is 58%-62%; the molecular weight of the xanthan gum is 1 million-2 million; the particle size of the polysaccharide gum in the ultrafine polysaccharide gum aqueous solution is less than 10 μm; (2) spraying the ultrafine polysaccharide glue solution on the surface of cellulose or its derivatives by high-pressure atomization, and high-shear mixing to make the ultrafine polysaccharide glue solution penetrate into the interior of cellulose or its derivatives and bond to form micelles; the cellulose or its derivatives are sodium carboxymethyl cellulose or a mixture of sodium carboxymethyl cellulose and hydroxyethyl cellulose; the molecular weight of the sodium carboxymethyl cellulose is 20,000-80,000, and the degree of substitution of the sodium carboxymethyl cellulose is 0.7-0.9; the molecular weight of the hydroxyethyl cellulose is 100,000-200,000, and the degree of substitution is 1.3-1.5; the size of the micelles is 0.1-1 mm; (3) drying the micelles by microwave vacuum drying to form honeycombed micelles; (4) Using a spray fluidized bed granulation technology, water is sprayed on the surface of the honeycomb micro-clusters at high pressure and dried to obtain a hydrogel that absorbs oil; the process parameters of the spray fluidized bed granulation technology are an inlet air temperature of 10-30°C, a fan frequency of 20-50Hz, and an atomized water flow rate of 10-20g / min.
[0036] After the polysaccharide gum is mixed with water, it is wet-milled by a sand mill to make the size of the polysaccharide gum less than 10 microns, with a larger specific surface area, so more surface groups are exposed, such as -OH, -COOH, -COO-, -O-, -NH2, -NH-, -COOR, After high shear mixing, the ultrafine polysaccharide glue solution can quickly and evenly penetrate into the interior of cellulose or its derivatives and bond into micelles. Under high vacuum and low temperature, the interior of the micelles can be expanded to form a honeycomb structure by microwave heating. The honeycomb structure in the micelles can be re-combined with water and dehydrated again by spraying ultrapure water on the honeycombed micelles in a fluidized bed and boiling drying and granulation, thereby reducing the size of the honeycomb structure and increasing the entanglement strength between the molecular chains of the polysaccharide glue and the molecular chains of cellulose or its derivatives. The groups on the surface of the polysaccharide glue and the -OH or -COONa groups in cellulose or its derivatives form a three-dimensional network structure through hydrogen bonds. Combined with the dense honeycomb structure, it has a stronger water absorption capacity and a faster water absorption speed, which can greatly improve the feeling of fullness after consumption. And due to the existence of the honeycomb structure and the ultrafine high-ester pectin, the hydrogel's adsorption capacity for oil is increased by more than 10 times, which can greatly reduce the absorption of oil in the body after consumption.
[0037] The change of esterification degree will affect the physical and chemical properties and structure of pectin, and further affect its functional characteristics. The esterification degree of the high ester pectin selected in the present invention is 58% to 62%. The increase or decrease of esterification degree will lead to the conformational change of pectin molecules, affect the formation of physical cross-linking sites, and ultimately affect the performance of hydrogels.
[0038] In some embodiments of the present invention, in step (1), the water is ultrapure water, which can avoid the influence of other ions and other substances and is conducive to the formation of a physical cross-linked network of the hydrogel.
[0039] In some embodiments of the present invention, in step (1), the concentration of the polysaccharide glue in the ultrafine polysaccharide glue aqueous solution is 0.01 kg / L to 0.1 kg / L.
[0040] The degree of substitution of sodium carboxymethyl cellulose will affect its stability and rheological properties. The present invention selects sodium carboxymethyl cellulose with a degree of substitution of 0.7-0.9 and hydroxyethyl cellulose with a degree of substitution of 1.3-1.5. The increase or decrease of the degree of esterification will increase the number of hydrophilic groups on its molecular chain and affect the formation of a physical cross-linked network.
[0041] In some embodiments of the present invention, in step (1), the mass ratio of the high ester pectin to the xanthan gum is greater than or equal to 3:1.
[0042] In some embodiments of the present invention, in step (1), the rotation speed of the wet ultrafine grinding is 1000-1500 rpm, and the time of the wet ultrafine grinding is 30-60 min. Preferably, the equipment used for the wet ultrafine grinding is a sand mill.
[0043] In some embodiments of the present invention, in step (2), the mass ratio of sodium carboxymethyl cellulose to hydroxyethyl cellulose is 10-15:4.98-9.98. Preferably, the mass ratio of sodium carboxymethyl cellulose to hydroxyethyl cellulose is 15:4.98 or 10:9.98.
[0044] In some embodiments of the present invention, in step (2), the rotation speed of the high shear mixing is 1000-1500 rpm, the high shear mixing time is 5-10 min, and finally a micro-agglomerate with a size of 0.1-1 mm is formed. Preferably, the equipment used for the high shear mixing is a high-speed shear mixer.
[0045] In some embodiments of the present invention, in step (2), the mass ratio of the polysaccharide glue in the ultrafine polysaccharide glue solution to the mass ratio of cellulose or its derivative is 0.01-0.1:9.9-9.99. Preferably, the mass ratio of the polysaccharide glue in the ultrafine polysaccharide glue solution to the mass ratio of cellulose or its derivative is 0.02:19.98 or 0.2:19.8.
[0046] In some embodiments of the present invention, in step (3), the vacuum degree of the microwave vacuum drying is -98.0 kPa to -100.0 kPa, the temperature of the microwave vacuum drying is 28 to 44° C., and the time of the microwave vacuum drying is 0.5 to 1 h.
[0047] In some embodiments of the present invention, in step (4), the water used in the high-pressure atomization spraying is ultrapure water.
[0048] In some embodiments of the present invention, in step (4), the drying is boiling drying in a fluidized bed, and the drying time is 0.5 to 1 hour.
[0049] In some embodiments of the present invention, the bulk density of the prepared oil-absorbing hydrogel is 0.5-0.7 g / ml.
[0050] The present invention also provides a grease-absorbing hydrogel prepared by any of the preparation methods described above, wherein the grease-absorbing hydrogel has a honeycomb structure. Preferably, the bulk density of the grease-absorbing hydrogel is 0.5-0.7 g / ml, and the hydrogel has a smaller unit volume, which is more conducive to swallowing by the user.
[0051] The present invention also provides a fat-absorbing hydrogel prepared by any of the above preparation methods or the use of the above fat-absorbing hydrogel in preparing food, medicine or health care products with diet control, satiety induction and weight loss effects.
[0052] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0053] In the present invention, the test method for the size of micelles is as follows: placing the micelles after high shear mixing on a sieve and sieving them. If there are micelles remaining on the sieve, replace the sieve with one with a smaller mesh number. The corresponding aperture of the sieve interval where the micelles are located is the size range of the micelles.
[0054] Table 1 Comparison of sieve mesh number and hole particle size
[0055] The xanthan gums with different molecular weights in the examples and the control group were homemade materials, and xanthan gums with different molecular weights were prepared using Ziboxan® KF xanthan gum (viscosity: 600-1800 cps) produced by Ordos Zhongxuan Biochemical Co., Ltd. as raw materials.
[0056] The specific preparation method is: 200g Ziboxan® KF xanthan gum sample was placed in 20kg water, and after 40kHz ultrasonic treatment for 60, 90, 120, 150 or 160min, poured into a tray and placed in a forced air drying oven at 80°C for 24h, and after crushing, xanthan gum with a molecular weight of 2.5 million, 2 million, 1.6 million, 1 million or 800,000 was obtained.
[0057] Table 2 Manufacturers and product numbers of other raw materials
[0058] The molecular weight test methods of xanthan gum, sodium carboxymethyl cellulose, hydroxyethyl cellulose, high ester pectin and low ester pectin refer to "Pharmacopoeia of the People's Republic of China 0514 Molecular Exclusion Chromatography": Liquid chromatography parameters: TSK-GMPWxl chromatographic column (7.8mm×30.0cm), column temperature 50°C, mobile phase 0.05mol / L sodium sulfate solution, flow rate 0.5ml / min, injection volume 20μL, detector: differential refractometer.
[0059] Molecular weight calibration curve drawing: Weigh 1.5g of polydextrose standard samples with known molecular weights (DXT 500, DXT 3K, DXT 20K, DXT 200K, DXT 1185K, DXT 5900K, with weight average molecular weights of 505, 3650, 20100, 207200, 1185000, 5900000, respectively) and dissolve them in 0.05mol / L sodium sulfate solution, make the volume to 1L, filter through 0.45μm filter paper, and take 20μL of each sample to obtain the standard curve; Sample treatment: Weigh 1.5 g of sample, dissolve it in 0.05 mol / L sodium sulfate solution to 1 L, pass it through 0.45 μm filter paper, absorb 20 μL of sample, and test to obtain its molecular weight.
[0060] The test method for the degree of substitution of hydroxyethyl cellulose refers to "ASTM D4794-94 Standard Test Method for Ethoxy or Hydroxyethoxy Substitution in Cellulose Ether Products by Gas Chromatography": Gas chromatography conditions: column WAX, column temperature 100°C, detector is hydrogen flame detector, temperature is 250°C, vaporization chamber temperature is 200°C, injection volume: 1.0 μL.
[0061] Standard curve drawing: Standard solution preparation: 30μL (ethyl iodide) / 10mL (toluene), 40μL (ethyl iodide) / 10mL (toluene), 50μL (ethyl iodide) / 10mL (toluene), 60μL (ethyl iodide) / 10mL (toluene), 70μL (ethyl iodide) / 10mL (toluene). After the preparation is completed, inject the sample to obtain the standard curve.
[0062] Sample treatment: Weigh 0.0711g of dry sample, put it into a 15mL reactor, add 10mL of hydroiodic acid solution. Place the reactor in an oven at 180℃ for 2h. After the reaction, extract with 10mL of toluene twice, retain the extraction solution for gas chromatography test, and obtain the sample molar substitution after the test.
[0063] The degree of substitution of sodium carboxymethyl cellulose is determined according to the method in Appendix A.5 of GB 1886.232-2016 National Food Safety Standard Food Additive Sodium Carboxymethyl Cellulose.
[0064] Method for testing the degree of esterification of high-ester pectin and low-ester pectin: The degree of esterification of pectin was determined by Fourier transform infrared spectroscopy (FT-IR), where the COOCH and COOH groups were detected at 1740 cm -1 -- and ~1630cm -1 There is strong absorption at 1740cm. Qmnic 9.2 software was used to correct the spectral baseline and perform quantitative analysis. The calculation formula of degree of esterification (DE) is DE=A1740 / (A1740+A1630), where A1740 and A1630 represent 1740cm -1 and 1630cm -1 - The peak area at .
[0065] Example 1
[0066] 0.2 kg of high-ester pectin (molecular weight of 20,000, degree of esterification of 62%) was placed in 2 L of ultrapure water, and the high-ester pectin was wet-milled and ultrafinely ground for 30 min until the particle size of the high-ester pectin was less than 10 μm, and the speed of the sand mill was 1500 rpm. 19.8 kg of sodium carboxymethyl cellulose (molecular weight of 20,000, degree of substitution of 0.72) was placed in a high-speed shear mixer, and the high-ester pectin solution was sprayed on the surface of the sodium carboxymethyl cellulose by high-pressure atomization, and high-shear mixing was performed at the same time, the speed was 1500 rpm, and the high-shear mixing time was 5 min to form 0.1-0.5 mm micelles, and the formed micelles were placed in a microwave vacuum drying oven, and the vacuum degree was set to -98.0 kPa and the temperature was 44 ° C. After drying for 0.5 h, the micelles were taken out and placed in a fluidized bed, and the inlet air temperature was set to 10 ° C, the fan frequency was 50 Hz, and the atomized water flow rate was 10 g / min. Ultrapure water was sprayed by high-pressure atomization and boiled for 1 h Then the composite gel 1 was obtained.
[0067] Example 2
[0068] The preparation method was consistent with that of Example 1, except that the molecular weight of high-ester pectin was 80,000 and the degree of esterification was 58%, thereby obtaining composite gel 2.
[0069] Example 3
[0070] The preparation method was consistent with that of Example 1, except that the molecular weight of high-ester pectin was 200,000 and the degree of esterification was 62%, thereby obtaining composite gel 3.
[0071] Example 4
[0072] The preparation method was consistent with that of Example 1, except that the molecular weight of sodium carboxymethyl cellulose was 50,000 and the degree of substitution was 0.75, to obtain composite gel 4.
[0073] Example 5
[0074] The preparation method was consistent with that of Example 1, except that the molecular weight of sodium carboxymethyl cellulose was 80,000 and the degree of substitution was 0.89, to obtain composite gel 5.
[0075] Example 6
[0076] The preparation method was consistent with that in Example 1, except that the speed of the sand mill was replaced with 1000 rpm, the grinding time was 60 min, the speed of the high-speed shear mixer was replaced with 1000 rpm, the mixing time was 10 min, and 0.3-1 mm micelles were formed to obtain composite gel 6.
[0077] The longer the grinding and mixing time, the larger the micelles formed.
[0078] Example 7
[0079] The preparation method was consistent with that of Example 6, except that the sand mill speed was replaced with 1100 rpm, the grinding time was 55 min, the high-speed shear mixer speed was replaced with 1300 rpm, the mixing time was 7 min, and 0.3-0.9 mm micelles were formed to obtain composite gel 7.
[0080] Example 8
[0081] The preparation method was consistent with that of Example 1, except that the amount of high-ester pectin added was replaced with 0.02 kg and the amount of sodium carboxymethyl cellulose added was replaced with 19.98 kg, to obtain composite gel 8.
[0082] Example 9
[0083] The preparation method was consistent with that of Example 1, except that the amount of high-ester pectin added was replaced with 0.1 kg and the amount of sodium carboxymethyl cellulose added was replaced with 19.9 kg, to obtain composite gel 9.
[0084] Example 10
[0085] The preparation method was consistent with that in Example 1, except that the vacuum degree of the microwave vacuum drying oven was set to -100.0 kPa and the temperature was 28° C. to obtain composite gel 10.
[0086] Embodiment 11
[0087] The preparation method was consistent with that in Example 1, except that the inlet air temperature of the fluidized bed was replaced with 30° C., the fan frequency was 50 Hz, and the atomized water flow rate was 20 g / min, to obtain composite gel 11.
[0088] Example 12
[0089] The preparation method was consistent with that of Example 8, except that the polysaccharide gum was replaced with 0.015 kg of high-ester pectin and 0.005 kg of xanthan gum (molecular weight of 1 million) to obtain composite gel 12.
[0090] Example 13
[0091] The preparation method was the same as that of Example 8, except that the polysaccharide gum was replaced with 0.015 kg of high-ester pectin and 0.005 kg of xanthan gum (molecular weight of 2 million) to obtain composite gel 13.
[0092] Embodiment 14
[0093] The preparation method was consistent with that of Example 8, except that the polysaccharide gum was replaced with 0.015 kg of high-ester pectin and 0.005 kg of xanthan gum (molecular weight of 1.6 million) to obtain composite gel 14.
[0094] Embodiment 15
[0095] The preparation method was consistent with that of Example 8, except that the polysaccharide gum was replaced with 0.016 kg of high-ester pectin and 0.004 kg of xanthan gum (molecular weight of 1.6 million) to obtain composite gel 15.
[0096] Example 16
[0097] The preparation method was consistent with that of Example 8, except that the amount of carboxymethyl cellulose added was replaced with 15 kg of sodium carboxymethyl cellulose (molecular weight of 20,000, degree of substitution of 0.72) and 4.98 kg of hydroxyethyl cellulose (molecular weight of 100,000, degree of substitution of 1.5), to obtain composite gel 16.
[0098] Embodiment 17
[0099] The preparation method was consistent with that of Example 8, except that the amount of carboxymethyl cellulose added was replaced by 15 kg of sodium carboxymethyl cellulose (molecular weight of 20,000, degree of substitution of 0.72) and 4.98 kg of hydroxyethyl cellulose (molecular weight of 200,000, degree of substitution of 1.3), to obtain composite gel 17.
[0100] Embodiment 18
[0101] The preparation method was consistent with that of Example 8, except that the amount of sodium carboxymethyl cellulose added was replaced with 10 kg sodium carboxymethyl cellulose (molecular weight 20,000, degree of substitution 0.72) and 9.98 kg hydroxyethyl cellulose (molecular weight 160,000, degree of substitution 1.3), to obtain composite gel 18.
[0102] Control group 1
[0103] The preparation method was consistent with that of Example 1, except that the molecular weight of high-ester pectin was increased to 250,000 to obtain comparative gel 1.
[0104] Control group 2
[0105] The preparation method was consistent with that of Example 1, except that the esterification degree of high-ester pectin was reduced to 56%, thereby obtaining comparative gel 2.
[0106] Control group 3
[0107] The preparation method was consistent with that of Example 1, except that the esterification degree of high-ester pectin was increased to 63%, to obtain comparative gel 3.
[0108] Control group 4
[0109] The preparation method was consistent with that of Example 1, except that high-ester pectin was replaced by low-ester pectin with a molecular weight of 50,000 and a degree of esterification of 44%, to obtain comparative gel 4.
[0110] Control group 5
[0111] The preparation method was consistent with that of Example 1, except that the molecular weight of sodium carboxymethyl cellulose was increased to 100,000 and the degree of substitution was 0.75, thereby obtaining comparative gel 5.
[0112] Control group 6
[0113] The preparation method was consistent with that of Example 1, except that the degree of substitution of sodium carboxymethyl cellulose was reduced to 0.66 to obtain comparative gel 6.
[0114] Control group 7
[0115] The preparation method was consistent with that of Example 1, except that the degree of substitution of sodium carboxymethyl cellulose was increased to 0.95 to obtain comparative gel 7.
[0116] Control group 8
[0117] The preparation method was consistent with that of Example 1, except that the molecular weight of sodium carboxymethyl cellulose was reduced to 10,000 to obtain comparative gel 8.
[0118] Control group 9
[0119] The preparation method was consistent with that of Example 12, except that the polysaccharide gum was replaced with 0.01 kg of high-ester pectin and 0.01 kg of xanthan gum (molecular weight of 1 million) to obtain comparative gel 9.
[0120] Control group 10
[0121] The preparation method was consistent with that of Example 12, except that the polysaccharide gum was replaced with 0.005 kg of high-ester pectin and 0.015 kg of xanthan gum (molecular weight of 1 million) to obtain comparative gel 10.
[0122] Control group 11
[0123] The preparation method is consistent with Example 12, except that the molecular weight of xanthan gum is reduced to 800,000 to obtain comparative gel 11.
[0124] Control group 12
[0125] The preparation method is consistent with Example 12, except that the molecular weight of xanthan gum is increased to 2.5 million to obtain comparative gel 12.
[0126] Control group 13
[0127] The preparation method was consistent with that of Example 17, except that the molecular weight of hydroxyethyl cellulose was reduced to 80,000 and the degree of substitution was 1.5, to obtain comparative gel 13.
[0128] Control group 14
[0129] The preparation method was consistent with that of Example 17, except that the molecular weight of hydroxyethyl cellulose was increased to 250,000 and the degree of substitution was 1.5, to obtain comparative gel 14.
[0130] Control group 15
[0131] The preparation method was consistent with that of Example 17, except that the degree of substitution of hydroxyethyl cellulose was reduced to 1.1 to obtain comparative gel 15.
[0132] Control group 16
[0133] The preparation method was consistent with that of Example 17, except that the degree of substitution of hydroxyethyl cellulose was increased to 1.8 to obtain comparative gel 16.
[0134] Control group 17
[0135] 0.2 kg of high-ester pectin (molecular weight of 20,000, degree of esterification of 62%) was placed in 2 L of ultrapure water and stirred to dissolve for 30 min. 19.8 kg of sodium carboxymethyl cellulose (molecular weight of 20,000, degree of substitution of 0.72) was placed in a high-speed shear mixer. The high-ester pectin solution was poured on the surface of the sodium carboxymethyl cellulose and high-shear mixing was performed at a speed of 1500 rpm for 5 min to form 0.1-2.0 mm micelles. The formed micelles were placed in a microwave vacuum drying oven with a vacuum degree of -98.0 kPa and a temperature of 44 °C. After drying for 0.5 h, the micelles were taken out and placed in a fluidized bed with an inlet temperature of 10 °C, a fan frequency of 50 Hz, and an atomized water flow rate of 10 g / min. Ultrapure water was sprayed with high-pressure atomization and boiled for 1 h to form agglomerates to obtain comparative gel 17.
[0136] In this comparative example, the sand mill is not used for wet ultrafine grinding, and most of the high-ester pectin cannot be dissolved and sinks to the bottom, and the particle size reaches more than 100 μm, or even reaches the millimeter level. It is impossible to spray with high-pressure atomization, and the nozzle is easily blocked, so it can only be poured. Due to uneven pouring, the size of the formed micro-groups is relatively large, it is not easy to boil, and it is easy to clump.
[0137] Control group 18
[0138] The preparation method was consistent with that in Example 1, except that the speed of the sand mill was adjusted to 900 rpm and the grinding time was increased to 5 hours to obtain comparative gel 18.
[0139] In this comparative example, the speed of the sand mill is relatively low, and even if the grinding time is increased to 5 hours, the particle size of the high-ester pectin is still greater than 10 μm.
[0140] Control group 19
[0141] The preparation method is consistent with that in Example 1, but a high-speed shear mixer is not used to perform high-shear mixing on the sodium carboxymethyl cellulose sprayed with the ultrafine polysaccharide gel solution. The agglomeration is uneven, with large lumps and dry powder that cannot agglomerate. The large lumps cannot boil in the fluidized bed. After drying, the large lumps are crushed to obtain comparison gel 19.
[0142] Control group 20
[0143] The preparation method is consistent with that in Example 1, except that the rotation speed of the high-speed shear mixer is adjusted to 900 rpm. The obtained micelle particle size is 0.5-5 mm. The large-size micelle cannot boil in the fluidized bed. After drying, the large-size micelle is crushed to obtain the comparison gel 20.
[0144] Control group 21
[0145] The preparation method was consistent with that in Example 1, but instead of using a microwave vacuum drying oven to vacuum dry the micelles, an ordinary forced air drying oven was used to dry them, and finally a comparative gel 21 was obtained.
[0146] Ordinary drying oven drying cannot form a honeycomb structure.
[0147] Control group 22
[0148] The preparation method was consistent with that in Example 1, except that the air inlet temperature of the fluidized bed was adjusted to 8° C., but the target gel could not be obtained.
[0149] The air inlet temperature of the fluidized bed is too low, and the moisture cannot evaporate quickly, resulting in agglomeration and failure to form a dry gel.
[0150] Control group 23
[0151] The preparation method was consistent with that in Example 1, except that the fan frequency was reduced to 15 Hz, and the target gel could not be obtained.
[0152] The fluidized bed fan frequency is too low, the micro-clusters cannot boil, and the water cannot evaporate quickly, resulting in agglomeration and the inability to form a dry gel.
[0153] Control group 24
[0154] The preparation method was consistent with that in Example 1, except that the atomized water flow rate was increased to 22 g / min, and the target gel could not be obtained.
[0155] The sprayed atomized water cannot evaporate quickly, resulting in gradual agglomeration and failure to obtain a dry gel.
[0156] Control group 25
[0157] The preparation method was consistent with that of Example 1, but high-pressure atomization spraying of ultrapure water was not performed during boiling drying, and comparative gel 25 was obtained.
[0158] Ultrapure water was not sprayed during boiling drying, so the pore size of the honeycomb structure could not be miniaturized, the packing density was low, and because the honeycomb structure was too loose, the modulus after water absorption was low.
[0159] Control group 26: only sodium carboxymethylcellulose was used without adding polysaccharide gum
[0160] Take 20kg of sodium carboxymethyl cellulose (molecular weight of 20,000, degree of substitution of 0.72) and place it in a high-speed shear mixer. Spray ultrapure water on the surface of the sodium carboxymethyl cellulose by high-pressure atomization, and perform high-speed shearing at a rotation speed of 1500rpm and a mixing time of 5min to form 0.1~0.5mm micelles. Place the formed micelles in a microwave vacuum drying oven, set the vacuum degree to -98.0kPa, the temperature to 44°C, dry for 0.5h, take out and place in a fluidized bed, set the inlet temperature to 10°C, the fan frequency to 50Hz, and the atomized water flow rate to 10g / min. Ultrapure water is sprayed by high-pressure atomization and boiled for 1h before taking out to obtain comparison gel 26.
[0161] Sodium carboxymethyl cellulose alone cannot form a three-dimensional network structure, so it will clump when it comes into contact with water, making it impossible to test the modulus and unable to absorb oil.
[0162] Control group 27
[0163] The sample was prepared according to the method of Example 1 of patent CN17179281A, i.e., 3 g of high-ester pectin was placed in 3.33 L of ultrapure water and stirred to dissolve, 200 g of sodium carboxymethyl cellulose was added to the high-ester pectin solution and stirred for 2 h, then placed in a forced air drying oven at 110°C for 8 h, and then crushed into particles of 20-50 mesh after drying to obtain comparison gel 27.
[0164] 1. Water absorption test method: Take 1 g of composite gel or contrast gel and place it in a medium with artificial gastric juice: water at a ratio of 1:8, place it in a 37 ℃ incubator for 30 minutes, filter out the water with a stainless steel sieve and weigh it. The weight of the hydrogel after water absorption is m1. Water absorption multiple = (m1-1) / 1. Artificial gastric juice is prepared according to the method of Chinese Pharmacopoeia.
[0165] 2. Storage modulus test method: Wipe off the moisture on the surface of the sample obtained from the above test on the water absorption multiple, place it between the parallel plates (25 mm) of the rotational rheometer, fix the tension at 0.5%, fix the frequency range at 1-50 rad / s, and take the storage modulus value corresponding to the frequency of 10 rad / s as the storage modulus G of the sample.
[0166] 3. Water absorption speed test method: Take 1 g of composite gel or control gel respectively and place it in a medium of artificial gastric juice: water at a ratio of 1:8, place it in a 37 ℃ incubator for 10s, 30s, 60s, and 120s, then take it out, filter out the water with a stainless steel sieve and weigh it. The weight of the hydrogel after water absorption is m2. Water absorption multiple = (m2-1) / 1. Artificial gastric juice is prepared according to the Chinese Pharmacopoeia method.
[0167] 4. Grease absorption capacity test method: Take 1 g of composite gel or contrast gel and place it in 200 ml of a medium with a ratio of 1:1 vegetable oil to water. Place it in a 37 ℃ incubator and stir for 30 minutes. Use a stainless steel sieve to filter out the mixture of oil and water. Use a separatory funnel to separate the oil and water in the filtrate. The volume of the tested vegetable oil is V1. The volume of vegetable oil absorbed by 1 g of composite gel or contrast gel is = 100 ml - V1.
[0168] 5. Bulk density test method: Take 1 g of composite gel or control gel and place it in a 5 ml measuring cylinder. Visually observe the volume V2. The bulk density is = 1 / V2. Analysis and Conclusion
[0169] Table 3 Water absorption multiples, storage modulus, oil absorption volume, and bulk density of samples in the examples and control group
[0170]
[0171]
[0172] Table 4 Water absorption rate of the examples and control group samples
[0173]
[0174]
[0175] Table 5 The amount of polysaccharide glue, amount of solvent, drying time, and energy consumption used in preparing the same sample amount (20 kg) in Examples 1-18 and Control Group 27
[0176]
[0177] Note: The power of microwave drying oven with the same production capacity is 36kw, the power of blast drying oven is 36kw, and the combined power of fluidized bed fan and peristaltic pump is 6kw.
[0178] Control groups 1-16 showed that the selection and ratio of raw materials would have a great influence on the comprehensive performance of the prepared hydrogel. It is necessary to comprehensively consider factors such as the molecular weight and degree of esterification of high-ester pectin, the molecular weight of xanthan gum, the ratio of high-ester pectin and xanthan gum, the molecular weight and degree of substitution of sodium carboxymethyl cellulose, and the molecular weight and degree of substitution of hydroxyethyl cellulose. By synergistically adjusting the proportions and characteristics of each raw material, the prepared hydrogel can have excellent oil absorption capacity while also having a high water absorption multiple, a large storage modulus and a faster water absorption rate.
[0179] Since the control group 17 was not subjected to wet ultrafine grinding by a sand mill, it could not be sprayed but only poured, so the material quickly agglomerated to form lumps, and the interior of the lumps was unwetted sodium carboxymethyl cellulose, and the overall dispersion was extremely uneven. Therefore, the comparative gel 1 formed had a low water absorption multiple, uneven modulus, and weak oil absorption capacity.
[0180] In the control group 18, the low speed of the sand mill resulted in larger pectin particle size, low physical cross-linking efficiency and uneven cross-linking, and weak water and oil absorption capacity of the hydrogel.
[0181] The control group 19 did not use a high-speed shear mixer to perform high-shear mixing on the sodium carboxymethyl cellulose sprayed with the ultrafine polysaccharide gel aqueous solution, and the agglomeration was uneven, with large agglomerates and dry powder that could not agglomerate. The large agglomerates could not boil in the fluidized bed, and the obtained gel had weak water and oil absorption capabilities.
[0182] In the control group 20, due to the slow speed of the high shear mixer, the obtained micro-agglomerate particle size was too large and could not boil in the fluidized bed, so the material was easy to clump together, with uneven dispersion, low water absorption and uneven modulus.
[0183] Since the control group 21 was not vacuum dried in a microwave vacuum drying oven, a honeycomb structure could not be formed, and thus the water absorption multiple was low.
[0184] In the control group 22, the air inlet temperature of the fluidized bed was too low, and the water could not evaporate quickly, resulting in agglomeration and failure to form a dry gel.
[0185] In the control group 23, the fan frequency of the fluidized bed was too low, the micro-clusters could not boil, and the water could not evaporate quickly, resulting in agglomeration and failure to form a dry gel.
[0186] The atomized water sprayed in the control group 24 could not evaporate quickly due to too fast flow rate, resulting in gradual agglomeration and failure to obtain a dry gel.
[0187] The control group 25 was not sprayed with atomized water during boiling drying, so the pore size of the honeycomb structure could not be miniaturized, the packing density was low, and the modulus after water absorption was low because the honeycomb structure was too loose.
[0188] In the control group 26, since sodium carboxymethyl cellulose alone cannot form a three-dimensional network structure, it will clump when it comes into contact with water, and the modulus cannot be tested and oil cannot be absorbed.
[0189] The water absorption performance of Examples 1-18 using the process of the present invention is improved by more than 50% compared with the control group 27, the water absorption speed is increased by about 1 times, and the oil absorption capacity is increased by more than 13 times. Pectin has certain lipophilic properties. After wet ultrafine grinding by a sand mill, the contact area with oil is greatly increased. Combined with the honeycomb structure, its oil absorption capacity is greatly enhanced. In preparing the composite gel of the same sample amount, the amount of high-ester pectin and solvent water used in Examples 1-18 is less, which can save raw material costs (the price of high-ester pectin is more than 5 times the price of sodium carboxymethyl cellulose, and the water consumption is reduced by more than 99%); the drying time is shortened by more than 75%, and the energy consumption is reduced by more than 85.41%.
[0190] Figure 1 This is a scanning electron microscope microscopic image of the composite gel 1 prepared in Example 1. The surface of the composite gel 1 sample was subjected to gold spraying treatment, and the sample surface was analyzed using a scanning electron microscope with parameters of 15.0 kV and 500×. The surface microstructure of the composite gel 1 showed a honeycomb porous structure.
[0191] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a hydrogel for absorbing oil, characterized in that: The following steps are involved: (1) mixing polysaccharide gum and water to obtain a mixed solution, and wet-milling the mixed solution to form an ultrafine polysaccharide gum aqueous solution; The polysaccharide gum is high-ester pectin or a mixture of high-ester pectin and xanthan gum; the molecular weight of the high-ester pectin is 20,000-200,000, and the degree of esterification of the high-ester pectin is 58%-62%; the molecular weight of the xanthan gum is 1 million-2 million; the particle size of the polysaccharide gum in the ultrafine polysaccharide gum aqueous solution is less than 10 μm; the rotation speed of the wet ultrafine grinding is 1000-1500 rpm, and the time of the wet ultrafine grinding is 30-60 minutes; (2) spraying the ultrafine polysaccharide glue solution on the surface of cellulose or its derivatives by high-pressure atomization, and high-shear mixing to make the ultrafine polysaccharide glue solution penetrate into the interior of cellulose or its derivatives and bond to form micelles; the cellulose or its derivatives are sodium carboxymethyl cellulose or a mixture of sodium carboxymethyl cellulose and hydroxyethyl cellulose; the molecular weight of the sodium carboxymethyl cellulose is 20,000-80,000, and the degree of substitution of the sodium carboxymethyl cellulose is 0.7-0.9; the molecular weight of the hydroxyethyl cellulose is 100,000-200,000, and the degree of substitution is 1.3-1.5; the size of the micelle is 0.1-1 mm; the rotation speed of the high-shear mixing is 1,000-1,500 rpm, and the high-shear mixing time is 5-10 min; (3) drying the micelles by microwave vacuum drying to form honeycombed micelles; the vacuum degree of the microwave vacuum drying is -98.0 kPa to -100.0 kPa, the temperature of the microwave vacuum drying is 28 to 44° C., and the time of the microwave vacuum drying is 0.5 to 1 h; (4) Using a spray fluidized bed granulation technology, water is sprayed on the surface of the honeycomb micro-clusters at high pressure and dried to obtain a hydrogel that absorbs oil; the process parameters of the spray fluidized bed granulation technology are an inlet air temperature of 10-30°C, a fan frequency of 20-50Hz, and an atomized water flow rate of 10-20g / min.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the high ester pectin to the xanthan gum is greater than or equal to 3:
1.
3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the polysaccharide glue in the ultrafine polysaccharide glue aqueous solution is 0.01kg / L~0.1kg / L.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of sodium carboxymethyl cellulose to hydroxyethyl cellulose is 10-15:4.98-9.
98.
5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the polysaccharide glue in the ultrafine polysaccharide glue aqueous solution to the mass ratio of the cellulose or its derivative is 0.01-0.1:9.9-9.
99.
6. The preparation method according to claim 1, characterized in that: In step (4), the drying is performed by boiling in a fluidized bed, and the drying time is 0.5 to 1 hour.
7. The preparation method according to claim 1, characterized in that: The bulk density of the oil-absorbing hydrogel is 0.5-0.7 g / ml.
8. The oil-absorbing hydrogel prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The oil-absorbing hydrogel has a honeycomb structure.
9. Use of a fat-absorbing hydrogel prepared by the preparation method according to any one of claims 1 to 7 or a fat-absorbing hydrogel according to claim 8 in preparing food, medicine or health care products with the effects of controlling diet, inducing satiety and losing weight.
Citation Information
Patent Citations
High-expansion-coefficient weight control product and preparation process thereof
CN111772180A
Edible hydrogel, preparation method and application of edible hydrogel, and intragastric filler containing edible hydrogel
CN113854567A
Chitosan and flaxseed gum cross-linked hydrogel, preparation method and application of chitosan and flaxseed gum cross-linked hydrogel in gastric filler
CN115154407A
Water-soluble nanometer sustained-release functional coenzyme Q10 micro-capsule, method for preparing same and application of water-soluble nanometer sustained-release functional coenzyme Q10 micro-capsule
CN106727441A
Preparation method and application of intragastric volume-occupying hydrogel particles for obesity intervention
CN116807980A
Cited By
Hydrogel for improving satiety and preparation method and application thereof
CN120036474A
A hydrogel for improving satiety and its preparation method and application
CN120036474B
Hydrogel with weight losing effect as well as preparation method and application thereof
CN120092943A
A hydrogel with weight loss effect and its preparation method and application
CN120092943B